Total pattern analyses for non-crystalline materials. Issue 2 (June 2020) - Fawcett, T. G.; Gates-Rector, S.; Gindhart, A. M.; Rost, M.; Kabekkodu, S. N.; Blanton, J. R.; Blanton, T. N.
Abstract : A total pattern analysis suite of programs has been developed and incorporated into the ICDD ® PDF-4 database. While the suite of programs is intended for the analysis of any diffraction pattern, particular attention was focused on the analysis of common amorphous, non-crystalline, or partially crystalline materials found in minerals, polymers, and pharmaceuticals. The suite of programs directly interfaces to the ICDD database and libraries of non-crystalline references.